Quality of water supply on low cost housing in Shah Alam / Nuraina Asmaa Rejemat - Rejemat, Nuraina Asmaa (Faculty of Architecture, Planning and Surveying, 2013)
Water is one of the essential substance to all living thing .Water which is formed from a two chemical substance which is contains two hydrogen atom and an oxygen atom. This atom is bind by the covalent bond which is appearing in three state that is liquid state, gaseous state and also solid state. The example for solid state is ice and for gaseous state are water vapors. (Pollack , 2012)